Penyebarluasan Informasi KTH Muara Berau Biccu sebagai Upaya Pengenalan kepada Masyarakat - Muhammad Naufal Azhar; Angelita Sartika Pepayosa Nainggolan; Jasmine Maharani Rahman; Afrizal Muzacki; Andi Sarmilah; Fajrial Adzikra; Siti Rohana; Syarifah Nasywa; Nabila Aulia; Dhista Dwi Saputri; Akbar Lufi Zulfikar (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) conducted by Mulawarman University in Muara Badak Ulu Village, Kutai Kartanegara Regency, focused on introducing and strengthening the existence of the Muara Berau Biccu Forest Farmers Group (Kelompok Tani Hutan/KTH) to the wider community. This group plays an important role as a community forum for managing forests in a sustainable and equitable manner, encompassing the utilization of both timber and non-timber forest products. As part of the program, the students designed and implemented several activities aimed at raising public awareness and encouraging participation. The methods included creating an identity signboard for KTH as an official symbol of recognition, installing educational boards highlighting the importance of mangrove planting for coastal ecosystems, conducting mangrove planting using the silvofishery system that integrates environmental sustainability with aquaculture productivity, and developing a blog as a digital information platform accessible to the public. Through these initiatives, the program sought to enhance community knowledge about the ecological functions of mangrove forests, the importance of sustainable pond management for long-term productivity, and the benefits of having an online information medium to promote, document, and expand the networks of KTH Muara Berau Biccu. The results demonstrated an increased level of environmental awareness among community members, active participation in mangrove planting activities, and the establishment of a new communication medium that has the potential to strengthen the group’s position at both local and regional levels. Overall, the KKN program contributed significantly to supporting sustainable community-based forest and coastal resource management.